A point prevalence study of 150 patients with idiopathic retinal vasculitis: 1. Diagnostic value of ophthalmological features. Issue 9 (September 1989) - Graham, E M; Stanford, M R; Sanders, M D; Kasp, E; Dumonde, D C
Abstract : This paper describes the ophthalmological features of 150 patients with idiopathic retinal vasculitis, 67 of whom had isolated retinal vasculitis (RV) and 83 had RV associated with systemic inflammatory disease (RV + SID). The diagnosis of retinal vasculitis was made by ophthalmoscopy and fluorescein angiography, and patients with any identifiable cause (infection, ischaemia, or malignancy) were excluded from the study. Patients with isolated RV tended to have peripheral vascular sheathing, macular oedema, and diffuse capillary leakage. Those with RV accompanying Behçet's disease often had branch vein retinal occlusions and retinal infiltrates together with macular oedema and diffuse capillary leakage; the retinal infiltrates were pathognomonic for Behçet's disease. In sarcoidosis the retina typically showed features of periphlebitis associated with focal vascular leakage. Patients with uveomeningitis, multiple sclerosis, arthritis, or systemic vasculitis showed diffuse retinal capillary leakage associated with a mixture of the other features. Poor visual function was particularly associated with macular oedema and branch vein retinal occlusion, while the retina appeared to 'withstand' the impact of vascular sheathing, periphlebitis, or neovascularisation alone. Within the limitations of a point prevalence study it was concluded that different patterns of retinal vasculitis occur in different systemic inflammatory diseases, and that in isolated retinal vasculitis there is a particular association between peripheral vascular sheathing, macular oedema, and diffuse capillary leakage. In Part 2 we describe the results of examining the sera of these patients for the presence of antiretinal antibodies and circulating immune complexes.